1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

[Integrals] Just can't quite finish this

  1. Aug 31, 2004 #1
    Hi,

    I am trying to solve this problem:
    Find the right rieman sum and the integral (using the definition of integral) of:
    (-x^2/3)-7 on the interval [0,4] using n subintervals.

    So:
    lim n->infinity of [sigma from i = 1 to n of (-(4i/n)^2/3)-7]*4/n

    = lim n->infinity of [sigma from i = 1 to n of (-4i^2/3n^2)-7]*4/n
    = lim n->infinity of [sigma from i = 1 to n of i^2 - 7]*(-16/4n^3)
    = lim n->infinity of [sigma from i = 1 to n of i^2] - 7n*(-16/4n^3)
    = lim n->infinity of ((n(n + 1)(2n + 1))/6)-7n*(-16/4n^3)

    I don't how to go any farther with this...

    Thanks for any help.
     
  2. jcsd
  3. Aug 31, 2004 #2

    Hurkyl

    User Avatar
    Staff Emeritus
    Science Advisor
    Gold Member

    Well, you have lots of techniques for working with limits. For instance, you can usually break lim (A + B) into lim A + lim B. You can combine your fractions into a single fraction, and use what you know about limits of rational functions. If you think the result looks unreasonable, you can check your algebra. Et cetera.
     
  4. Aug 31, 2004 #3
    OK here we go:

    = lim n->infinity of ((n(n + 1)(2n + 1))/6)-7n*(-16/4n^3)
    = lim n->infinity of ((2n^3+3n^2+n)/6)+(112n/4n^3)
    = lim n->infinity of ((2n^3+3n^2+673n)/24n^3)
    = (1/12)+(1/8n)+(673/24n^2)
    = 1/12

    I know this is wrong though...
     
  5. Sep 1, 2004 #4

    Galileo

    User Avatar
    Science Advisor
    Homework Helper

    I had a hard time decyphering what you typed. It's a bit difficult to oversee.
    Try using LaTeX. (Click on the equations to see how it is used.)
    It's much more neat too. :wink:

    Anyway, you have:
    [tex]\sum_{i=1}^{n}f(x_i)\Delta x[/tex]
    [tex]f(x)=-\frac{x^2}{3}-7[/tex]
    [tex]x_i=\frac{4i}{n}[/tex]
    [tex]\Delta x=\frac{4}{n}[/tex]

    So the sum is:
    [tex]\sum_{i=1}^{n}\left(-\frac{16i^2}{3n^2}-7\right)\frac{4}{n}=-\frac{64}{3n^3}\sum_{i=1}^{n}i^2-\frac{28}{n}\sum_{i=1}^{n}1[/tex]
    Here I've just split the sum into two in the last step. (I think you got this right).

    Now for the first sum, use the identity:
    [tex]\sum_{i=1}^{n}i^2=\frac{1}{6}n(n+1)(2n+1)[/tex]
    So that:
    [tex]-\frac{64}{3n^3}\sum_{i=1}^{n}i^2=-\frac{64}{3n^3}\frac{1}{6}n(n+1)(2n+1)=-\frac{64}{18n^2}(2n^2+3n+1)[/tex]
    Then take the limit [itex]n\rightarrow \infty[/itex]
    The first sum becomes [itex]-\frac{64}{9}[/itex]

    The second sum is easy.

    Simple integration of the first term gives:
    [tex]\int_0^4\frac{-x^2}{3}dx = \frac{-x^3}{9}|^4_0=-\frac{64}{9}[/tex]
    Which matches the sum. :smile:

    PS: I`m glad we got the old smilies back, the new ones looked silly.

    Edit: Corrected a silly mistake
     
    Last edited: Sep 1, 2004
  6. Sep 1, 2004 #5

    Hurkyl

    User Avatar
    Staff Emeritus
    Science Advisor
    Gold Member

    Your calculus seems correct: you just need to work on your algebra skills. I think it would pay off for you to dig out your old texts and review.

    The big thing you're missing here is the distributive law: (a + b) c = a c + b c, which holds for sums also [itex]c \sum (a + b) = c \sum a + c \sum b[/itex].


    In particular:

    lim n->infinity of [sigma from i = 1 to n of (-4i^2/3n^2)-7]*4/n
    = lim n->infinity of [sigma from i = 1 to n of i^2 - 7]*(-16/4n^3)

    When you factor something out of a sum, you have to factor it out of every term, not just one of them.

    lim n->infinity of [sigma from i = 1 to n of i^2 - 7]*(-16/4n^3)
    = lim n->infinity of [sigma from i = 1 to n of i^2] - 7n*(-16/4n^3)

    Conversely, when you expand, each term gets multiplied by the outside constant. Also, you can't just pull additive constants out of a sum. Remember that [itex]\sum (a + b) = \sum a + \sum b[/itex]

    lim n->infinity of ((2n^3+3n^2+n)/6)+(112n/4n^3)
    = lim n->infinity of ((2n^3+3n^2+673n)/24n^3)

    And don't forget that when you add fractions that you have to set up a common denominator before you can simply add the numerators. 1/2 + 3/5 is not 4/10... it's 5/10 + 6/10 = 11/10
     
  7. Sep 1, 2004 #6
    Thanks guys I eventually figured out the rest of it!

    I have another simple algebra problem (doing another problem like this now). How do I isolate the variable i here?:

    lim n->infinity 5/n*sigma i = 1 to n of [(25-(5i/n)^2)^(1/2)]

    Thanks.
     
  8. Sep 1, 2004 #7

    Hurkyl

    User Avatar
    Staff Emeritus
    Science Advisor
    Gold Member

    You don't. :frown:

    To do this limit, I think you either need to do some estimation (and prove that the error goes to zero as n goes to infinity), or find some other way to evaluate the integral.
     
  9. Sep 2, 2004 #8
    Ah I noticed it finally. The area under that curve is a quarter circle with radius 5! Wow I'm so dumb sometimes. I got it now. Thanks. :)
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?



Similar Discussions: [Integrals] Just can't quite finish this
  1. I just can't get this (Replies: 3)

  2. Quite a complex integral (Replies: 17)

Loading...